Sign language detection and conversion to readable Bengali words using BdSL - Dhrubo, Tahsinul Haque; Mahmood, ASM Tareq; Tabassum, Noshin; Khan, Riead Hasan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science, 2023.